BUREAUCRATIC SIMPLIFICATION: CHANGES IN ORGANIZATIONAL STRUCTURE FROM STRUCTURAL TO FUNCTIONAL IN THE CENTRAL JAVA PROVINCIAL GOVERNMENT - Maria Susiawati; Hari Nugraha; Anon Priyantoro (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Bureaucracy still faces inefficiency and ineffectiveness problems while facing the challenges of very dynamic strategic environmental changes, for this reason the government has launched a bureaucratic simplification program implemented by the Central Java Provincial Government starting in 2021. However, the implementation of this policy has not been optimal. This study examines the changes in six elements of organizational structure from structural to functional in the implementation of bureaucratic simplification. The theory of mechanical and organic organizations is used to describe the nature of structural and functional organizational structures. A qualitative approach with descriptive methods and data collection from interviews and literature reviews have been used in this study. Interviews were conducted with informants from four OPDs in the Central Java Provincial Government, namely the Legal Bureau of the Regional Secretariat, Bappeda, the Agriculture and Plantation Service, and the Investment and One-Stop Integrated Service Service. The literature review was in the form of a review of several theories/concepts and related regulations. The study found that there had been a pseudo change, the characteristics of a structural mechanical organization were still maintained, managerial tasks in 4-6 layers, rigid and homogeneous departmentalization, a chain of command with vertical communication flow, a tall span of control, and centralized decision making. Changes towards organic organization are obtained from the teamwork approach in carrying out work. More appropriate changes in organizational structure in simplifying bureaucracy have been explained. The study recommends the elimination of coordinators and sub-coordinators with managerial duties permanently in the organizational structure of OPD, the implementation of a team-based work system, and the development of employee professionalism and competence as prerequisites for a functional organization that is responsive to change. Academic recommendations in the form of research on simplificationbureaucracy that focuses on the categorization/level of change of OPD from mechanical to organic organizations, research on competency and career development for functional positions, and research on the effectiveness of the new squad system work system.